Ohmic Heating: A potential technology for sweet whey processing. (April 2018) - Costa, Naiara R.; Cappato, Leandro P.; Ferreira, Marcus Vinicius S.; Pires, Roberto P.S.; Moraes, Jeremias; Esmerino, Erick A.; Silva, Ramon; Neto, Roberto P.C.; Tavares, Maria Inês B.; Freitas, Mônica Q.; Silveira Júnior, Raimundo N.; Rodrigues, Flávio N.; et al.
Abstract: The use of Ohmic Heating (OH) for sweet whey processing was investigated in this study. Whey samples were subjected to both different OH parameters (2, 4, 5, 7 and 9 V·cm −1 at 60 Hz, up to 72–75 °C/15 s) and conventional processing (72–75 °C/15 s). Physicochemical analyses (pH), color measurements ( L*, a*, b* ), rheological properties (flow curves and particle size distribution), microstructure (optical microscopy), bioactive compounds (ACE and antioxidant capacity), microbiological characterization (mesophilic bacteria, total coliforms, and thermotolerant coliforms), water mobility (TD-magnetic resonance domain), and sensory evaluation (descriptive analysis) were carried out. The OH effects on sweet whey characteristics depended on the applied electric field intensity. Higher saturation, higher color variation (ΔE*), and higher luminosity ( L* ) were observed in low electric fields. For bioactive compounds, the increase of the electric field negatively affected the preservation of the antioxidant capacity and the ACE Inhibitory Activity of bioactive peptides. OH and conventional samples exhibited a pseudo-plastic behavior ( n  < 1). OH performed at 4 and 5 V·cm −1 was able to provide similar levels of sensory profile and higher volatile compounds levels. The results suggested the OH technology as an interesting alternative to whey processing. Graphical abstract: Unlabelled Image Highlights: Sweet Whey submitted to Ohmic Heating (OH) Adequate hygienic – sanitary quality Greater preservation of bioactive compounds and volatile profiling Decreased luminosity and highlighted the green color Similar sensory profile of sweet whey compared to conventional process